Preference, importance and participation of girls and boys in the Physical Education High School class - So, Marcos Roberto; Martins, Mariana Zuaneti; Rodrigues, Gilson Santos; Prodocimo, Elaine; Ushinohama, Tatiana Zuardi; Betti, Mauro [UNESP] (Univ Nac La Plata, Fac Humanidades & Ciencias Educ, 2021)
The aim of this study is to understand, from the student's perspective, the interference of gender marker in High School students in relation to Physical Education (PE). This is a descriptive study with 94 boys and 88 girls from 8 public schools of Sao Paulo State (Brazil), which raised information on preference, importance and participation in PE classes, through the application of a structured questionnaire. The results indicate that boys give greater importance to like and participate more in the class than girls. However, it is not possible to say that girls dislike it, do not participate and do not give importance to it. Research in the literature shows that the participation of students in PE, beyond preference, is associated with the obligation or via subversive obedience in the ambiguous school environment, with explicit speeches of equal conditions and implicit gender segregationist practices. On the other hand, the implicit environment supports the colonization of boys in PE classes. We conclude that teachers (men and women) are the ones who can problematize inequality and assist students to establish gender equity PE.
Keywords: Gender; High School; Physical Education